Social functioning in bipolar disorder: investigating the role played by comorbid physical illnesses and cognition - Isabela Martins Becattini Pereira; Lucas Machado Mantovani; Gabriel Anselmo Frota; Raphael Rocha Wenceslau; Juliana Cunha Matos; Breno Fiuza Cruz; Antônio Lúcio Teixeira; Izabela Guimarães Barbosa (Dementia & Neuropsychologia)
ABSTRACT Bipolar disorder (BD) is a psychiatric disorder associated with functioning and cognitive impairments, as well as a higher prevalence of physical disease comorbidities. Objective: To determine the main predictors of functioning in patients with BD. Methods: Thirty-five patients with BD type I in remission participated in this study. To better characterize the degree of impairment, 20 matched controls were also studied. Functioning was assessed through the Functioning Assessment Short Test (FAST) and the UCSD Performance-based Skills Assessment (UPSA), while cognition was assessed through the BAC-A. Current physical conditions were assessed and categorized according to the Cumulative Illness Rating Scale (CIRS). Regression analyses were performed to examine the relationship between functioning and clinical variables, global cognitive performance, and physical comorbidities in BD. Results: UPSA correlated positively with the BAC-A total score (r=0.488; p=0.025), years of education (rho=0.41; p<0.01), and CIRS total score (rho=0.394; p<0.001). CIRS was the only predictor that remained negatively and significantly correlated with the UPSA total score (R2=0.446, F (1, 33)=8.198, p=0.007). Conclusion: Patients with BD had poor functioning, with the primary determinant of poor functioning being the burden of physical illnesses. In addition, the low agreement between the FAST and UPSA scales suggests these tolls assess distinct constructs.